An study of possible economic impacts on uruguayan dairy farms from inflation and devaluation changes - Álvarez, J.; Molina, C. (Agrociencia Uruguay, 2003)
The macroeconomic policy in Uruguay has changed since the 20th of June 2002, resulting in an increase of the devaluation and inflation rate, as recently observed . This study attempts to evaluate the impact of these changes on dairy farm financial performance. Simultaneously, a significant drop in milk prices in American dollars also took place. The methodology approach applied consisted in using three financial farm figures corresponding to the 2001-2002 period. These farms were selected from the FPTA Nº 100-Inia-Anpl-Facultad de Agronomía-Agrinet program. Changes were defined using two hypotheses about the inflation rate (50 y 70 %) and two about the devaluation rate (100 y 150 %). Three milk prices were evaluated (9, 10 y 11 American cents per litre). The farms were selected taking into account their production technology applied and their economic scale. The analysed variables were cost of production per litre, and the farm economic surplus. The primary conclusions showed a decrease on cost of production per litre , which depended on the level of dolarization of input costs. The financial performance was significantly affected although the cost drops, by the decrease in milk prices. The technologies that include a higher American dollar input component were more penalised. This analysis suggests the relevance to consider the inflation/devaluation ratio when the milk price is been analysed, given the high American dollar input component that characterised Uruguayan milk production.